Scarica l'intero Num. 4 (1994) di Classiconorroena (4Mb) (4Mb) - (a cura di), Redazione di Classiconorroena (Classiconorroena, 2014)
L. Martul Tobío, Anna Maranini, Fabio Stok, Riccardo Scarcia, Antonella Perelli, Teresa Pàroli, Paola Orlandi